Algunos aspectos limnológicos abióticos de las cuencas de los ríos Limay y Neuquén con especial referencia al embalse Ramos Mexía - Land de Castello, Helena (Ecosur, 2023)
The Negro river tributaries are the Limay and Neuquen rivers, which constitute the Andean eastern drainage system betweem 36" and 41" S. Huge reservoirs have been constructed, as a part of a hydroelectric power program and also for flood control purposes. Morphometric and lithological differences accounts for thermal and chemical distinctive fractures between these reservoirs. The Ramos Mexía impoundment and Pellegrini off-channel reservoir are wind mixed all over the year, while in the deeper Los Barreales and Mari Menuco stratification develops during the summer. The annual heat budget of the Ramos Mexía has been raughly estimated in 36131, 30760 and 31047 cal cm-2 for the years 1978, 1979-1980 and 1980-1981 respectively. These estimates are higher than those for others lakes situated on the Andes mountains in a region of more oceanic climate. The waters of the system are well oxygenated, neutral and soft. The Limay basin waters are the more diluted, with an average conductivity of 30 μScm-1 near the glacial lake Nahuel Huapi, and 67 μScm-1 in the Ramos Mexía artificial lake. Conductivity seasonal changes are related with discharge flow rate patterns and with level changes in the reservoirs. The Neuquen basin waters present conductivities ranging from 75 μScm-1 near the Andes, to 250 μScm-1 in Mari Menuco reservoir, while the Pellegrini attains to 3600 μScm-1. Both rivers (and R. Mexía artificial lake) have calcium-bicarbonate type waters, beeoming richer in sulphate and sodium as they move seaward through a semiarid region. In Los Barreales and M. Menuco reservoirs bicarbonate and sulphate may change their relative positions during the annual hydrologic cycle. The Pellegrini dosed basin belong to the sulphate-chloride sodium type. Reactive silica concentration is rather high throughout the year, without showing depletion to any important extent due to biogenic activity, except in the Pellegrini artificial lake.